Campylobacter positivity and public health risks in live bird markets, Busia, Kenya: A value chain analysis - Mbai, Josephat; Njoroge, Samuel M.; Obonyo, M.; Otieno, C.; Owiny, M.; Fèvre, Eric M. (Hindawi Limited, 2022)
Introduction: Live bird markets (LBMs) provide integral hubs for 95% of poultry produced for food. Surveillance systems in LBMs serving smallholder farmers in sub-saharan Africa are often non-functional and data about public health risks and emerging pathogens are lacking. Studies in Kenya have reported 29% – 44% Campylobacter-prevalence in poultry. We analyzed such LBMs in Kenya for likely transmission of Campylobacter from poultry to humans.